Sports Marketing : A Global Approach to Theory and Practice - Ennis, Sean (Springer International Publishing, 2020)
Sports is big business. Most companies want to expand into global markets, enhance their brand and understand varying market conditions. This international textbook supports sports marketing students as they learn about the challenges and opportunities that are specific to the global sports industry. Written from the perspective of different stakeholders in the sports sector, such as fans, sports entity holders, clubs, sponsors and the sports media, it offers an holistic view of this evolving and ever-changing industry. Taking a truly global approach, the text helps students understand the current issues facing sports marketing professionals and is relevant across all regions of the world. Drawing on the author's years of industry and teaching experience it blends theory and practice with case studies including the International Olympic Committee and the Fédération Internationale de Football Association (FIFA). Crucially the book provides comprehensive coverageof hot topics such as sports governance, digital marketing and the globalisation of the sports product. Written in an accessible style and accompanied by a full suite of online resources, this textbook is for ideal anyone looking to excel as a sports marketer or progress within the wider sports industry and is suitable for Sports Marketing courses at undergraduate, postgraduate and MBA levels.